Hair cortisol concentration in patients with active central serous chorioretinopathy is elevated – a pilot study. Issue 4 (22nd November 2018) - Lenk, Janine; Sandner, Dirk; Schindler, Lena; Pillunat, Lutz E.; Matthé, Egbert
Abstract: Purpose: To investigate hair cortisol concentration (HCC), a biochemical correlate of long‐term cortisol output patterns, and its relationship to active central serous chorioretinopathy (CSC). Methods: Twenty‐six participants were included in this observational pilot study (11 patients with active CSC and 15 healthy controls). Hair cortisol concentrations (HCCs) were determined from 3 cm hair strands collected near the scalp from patients and controls as an index of cumulative cortisol secretion over the 3‐month period prior to hair sampling. Results: Patients with CSC exhibited higher HCCs (mean value: 20.14, 95% CI: 14.89–27.16 pg/mg) than healthy controls (mean value: 11.06, 95% CI: 8.63–14.22 pg/mg, p = 0.008). Group differences were not affected by relevant covariates (BMI, smoking status, sex). Conclusion: Patients with active CSC have increased HCC, supporting the fact that cortisol is a major player in CSC pathogenesis.